Respiratory Syncytial Virus associated hospitalisations in children up to 6 years of age in Italy: a systematic review - Bechini, Angela; Salvati, Cristina; Bonito, Benedetta; Del Riccio, Marco; Stancanelli, Enrica; Bruschi, Mario; Ionita, Giulia; Iamarino, Johanna; Bentivegna, Davide; Buscemi, Primo; Ciardi, Giulia; Cosma, Claudia; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Respiratory syncytial virus is a leading cause of respiratory hospitalisations in infants. This systematic review (registration number: CRD42021248309) aims to synthesise the available evidence on Respiratory Syncytial Virus-related hospitalisations among children aged 0 to 6 years in Italy. Methods. The literature search was conducted on PubMed, Embase, Scopus, and International HTA, covering the period from January 2000 to July 2022, with a focus on studies that reported information on Respiratory Syncytial Virus-associated hospitalisation in children aged 0-6 years in Italy. Results. Eight articles were included after screening 20,845 records. These retrospective studies reported that most hospitalisations were among those <1 year (71.5%-88.8%), infants aged <1 year were also at higher risk of hospitalisation in intensive care unit. Respiratory Syncytial Virus infections typically peaked December-February, with an atypical early start in August 2021. Subtype analysis showed alternating prevalence of Respiratory Syncytial Virus-A and Respiratory Syncytial Virus-B across different seasons. Coinfections were not uncommon (1.1%-37.4%), with rhinovirus and bocavirus being the most frequent. Conclusions. All infants at their first Respiratory Syncytial Virus season showed an increased risk of severe infection and hospitalisation, regardless of the gestational age at birth, compared to older participants. This systematic review will enrich the understanding about Respiratory Syncytial Virus disease and help support decisions regarding prevention efforts in Italy.